2017
DOI: 10.1051/shsconf/20173300080
|View full text |Cite
|
Sign up to set email alerts
|

Youth Online Political Participation: The Role of Facebook Use, Interactivity, Quality Information and Political Interest

Abstract: Abstract. This paper focuses on the role of Facebook use, interactivity with politicians, quality of information and political interest as the predictors of online political participation among youth. The paper argues that Facebook use, interactivity, quality of information and political interests have the potential to engender online political participation among Nigerian youth. Also, by offering them an avenue for acquiring political information necessary for making an informed political decision through del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
1
10
1
2
Order By: Relevance
“…However, this suggests further that, quality of information is an important determinant and positively correlated to OPP (Abdu et al, 2016). Also, previous research has also reported that, factors related to OPP can be influenced by Facebook information quality such as intention to participate in offline activities of politics (like involving in community and civic services) and individual interactivity (Abdu et al, 2017;Ahmad et al, 2019;Houston et al, 2015) as youth political involvement is often regarded as a significant element to a healthy democracy (Cammaerts et al, 2016;Gaby, 2017). This reveals that political participation of youth is an important field of research proven to be useful to academics and political stakeholders.…”
Section: Perceived Information Qualitymentioning
confidence: 85%
“…However, this suggests further that, quality of information is an important determinant and positively correlated to OPP (Abdu et al, 2016). Also, previous research has also reported that, factors related to OPP can be influenced by Facebook information quality such as intention to participate in offline activities of politics (like involving in community and civic services) and individual interactivity (Abdu et al, 2017;Ahmad et al, 2019;Houston et al, 2015) as youth political involvement is often regarded as a significant element to a healthy democracy (Cammaerts et al, 2016;Gaby, 2017). This reveals that political participation of youth is an important field of research proven to be useful to academics and political stakeholders.…”
Section: Perceived Information Qualitymentioning
confidence: 85%
“…This idea was supported by Abdu et al (2017) in their study social media use, political information quality on social media, and political tendencies in influencing the political participation of young people. They discovered the key aspects of political participation are social media, the quality of political information, and young people's political tendencies.…”
Section: Analyse and Evaluate Political Information Sources In Social Mediamentioning
confidence: 91%
“…On the side of the recipient, there are factors that influence which social media content individuals will expose themselves to (e.g., interest; Abdu et al, 2017;Macafee, 2013;Parmelee & Roman, 2019). For instance, politically interested individuals should be more likely to follow political leaders on Instagram (Parmelee & Roman, 2019) and to take part in online political activities such as sending or receiving political information (Abdu et al, 2017) or posting links, status updates or likes (Macafee, 2013).…”
Section: Impacts Of Followers' Interestsmentioning
confidence: 99%